Pengaruh Tingkat Kepercayan, Kualitas Produk dan Harga Terhadap Keputusan Pembelian pada Home Industri Gula Aren di Muara Bulian - Muryati, Muryati; Lubis, Wahya Iffa; Rosmawati, Sri (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of the level of trust, product quality, price on purchasing decisions for palm sugar in Muara Bulian. The research was conducted using quantitative descriptive research, the population of this research were all direct buyers of palm sugar in the city of Muara Bulian, namely 75 regular customers. The research results show that simultaneous and partial testing shows that each variable has a positive and significant effect on the decision to purchase palm sugar in Muara Bulian.